2014
DOI: 10.1007/s11356-014-2680-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mercury speciation in commercial fishes of the Brazilian Amazon

Abstract: Mercury is responsible for serious episodes of environmental pollution throughout the world, especially in the Amazon. This toxicity has led regulatory agencies to focus on fish as the target organism for protecting the health of humans and other sensitive organisms. Unfortunately, in the Amazon area, different sampling strategies and the wide variety of sampling areas and fish species make it extremely difficult to determine relationships across geographic regions or over time to ascertain historical trends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
1
35
0
2
Order By: Relevance
“…One of the largest dams in the world is located in Tucuruí ( Figure 1 ), and human exposure to high levels of mercury was recently demonstrated in riverine population in this area [ 34 ]. Mercury is bioaccumulated and biomagnified through the food chain and by piscivorous fish, which are the species that are typically consumed the most by riverine population [ 52 , 53 ]. These fish show the highest levels of contamination [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest dams in the world is located in Tucuruí ( Figure 1 ), and human exposure to high levels of mercury was recently demonstrated in riverine population in this area [ 34 ]. Mercury is bioaccumulated and biomagnified through the food chain and by piscivorous fish, which are the species that are typically consumed the most by riverine population [ 52 , 53 ]. These fish show the highest levels of contamination [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anthropogenic action leads to higher concentrations on biosphere and may expose animals of aquatic food chain to damage [ 5 ]. Many researches have reported that fishes and other seafood are the main sources of human contamination by low daily doses, in which about 90% of Hg is present on its organic form, leading to higher bioaccumulation and biomagnification [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury contamination is a long-standing environmental and social problem throughout the world, especially in the Amazon (Martín-Doimeadios et al, 2014;Berzas Nevado et al, 2010). The widespread use of mercury (Hg) in artisanal and small-scale gold mining has driven contamination of the environment and people, threatening biodiversity, human health and livelihoods of traditional population.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these studies suggest large-scale environmental disruption, with widespread contamination, affecting biodiversity Kehrig et al, 2008;Dolbec et al, 2001;Bidone et al, 1997;Porvari, 1995) and impacting health of local communities that relies on fish as a protein source (Martín-Doimeadios et al, 2014;De Oliveira Santos et al, 2000), including indigenous people (Barbosa et al, 1998;Basta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%